Tuber melanosporum spread within sub-optimal climatic zones is controlled by fruiting triggers and not mycorrhiza survival - Paul W. Thomas (Acta Mycologica, 2014)
Tuber melanosporum is the most valuable of all cultivatable truffle species. Farming of this species spans every continent with the exception of Antarctica. Tuber aestivum (syn. T. uncinatum) and Tuber brumale are truffle species that have similar host plant preference and a similar affinity for calcareous soils as T. melanosporum, but occur over a broader geographic zone. The geographic limit of T. melanosporum is thought to be climatically dictated but it is not known whether this is due to an impact on mycorrhizal survival or climatically-derived fruiting triggers. Here, data is compiled from five cultivated research sites in the climatically sub-optimal conditions of the UK in order to address this question. Here we show: